2022
DOI: 10.1093/nsr/nwac041
|View full text |Cite
|
Sign up to set email alerts
|

High-entropy-alloy nanoparticles with 21 ultra-mixed elements for efficient photothermal conversion

Abstract: Multi-metallic nanoparticles have been proven to be an efficient photothermal conversion material, for which the optical absorption can be broadened through the interband transitions (IBTs), but it remains a challenge to make the composition homogeneous distributing within the immiscible combinations. Here, assisted with the extreme-high evaporated temperature, ultra-fast cooling, and vapor-pressure strategy, the arc-discharged plasma method was employed to synthesize the ultra-mixed multi-metallic nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 45 publications
0
52
0
5
Order By: Relevance
“…Currently, most of these studies are limited to quinary composition spaces. However, also HEAs composed of 8, [19] 12, [20] 14, [21] 16, [2] 20, and even 21, [22] elements have been synthesized. Thus, studying these complex multi-elemental composition spaces is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of these studies are limited to quinary composition spaces. However, also HEAs composed of 8, [19] 12, [20] 14, [21] 16, [2] 20, and even 21, [22] elements have been synthesized. Thus, studying these complex multi-elemental composition spaces is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the above liquid (melting)-solid transformations to synthesize HEA nanoparticles, the vapor-solid direct transformations have also been applied for HEA nanoparticles preparation, and some unprecedented alloys were successfully prepared by this method directly from the gas phase. 44,87 For example, Feng et al 44 reported spark plasma to control the composition of HEA nanoparticles by mixing the different metal vapors (Figure 3D). Owing to the excellent fluidity of vapor and easy mixing, the prepared free-standing nanoparticles show a uniform single phase and can be applied for additive manufacturing.…”
Section: Plasma-based Gas-phase Synthesismentioning
confidence: 99%
“…In addition, by directing airflow through fixed channels and depositing on the surface, the three-dimensional (3D) nanostructure multicomponent alloy with various elements (IrCuPd and AuAgCuPdSi) was successfully fabricated (Figure 3E,F), showing great potential in nanodevices design. In addition, Liao et al 87 demonstrated using arcdischarging plasma for the synthesis of ultra-mixing 21 F I G U R E 3 Diversified syntheses of HEA nanoparticles. (A) Various rapid shock methods include microwave heating, mechanical ultrasonication, rapid radiative heating, and laser shock method.…”
Section: Plasma-based Gas-phase Synthesismentioning
confidence: 99%
See 2 more Smart Citations